VEGFR-3 is expressed on megakaryocyte precursors in the murine bone marrow and plays a regulatory role in megakaryopoiesis - Thiele, Wilko; Rothley, Melanie; Kuch, Vanessa; Quagliata, Luca; Sleeman, Jonathan P. (Blood, 2012)
VEGFR-3 is a transmembrane receptor tyrosine kinase that is activated by its ligands VEGF-C and VEGF-D. Although VEGFR-3 has been linked primarily to the regulation of lymphangiogenesis, in the present study, we demonstrate a role for VEGFR-3 in megakaryopoiesis. Using a human erythroleukemia cell line and primary murine BM cells, we show that VEGFR-3 is expressed on megakaryocytic progenitor cells through to the pro-megakaryoblast stage. Functionally, specific activation of VEGFR-3 impaired the transition to polyploidy of CD41(+) cells in primary BM cultures. Blockade of VEGFR-3 promoted endoreplication consistently. In vivo, long-term activation or blockade of VEGFR-3 did not affect steady-state murine megakaryopoiesis or platelet counts significantly. However, activation of VEGFR-3 in sublethally irradiated mice resulted in significantly elevated numbers of CD41(+) cells in the BM and a significant increase in diploid CD41(+) cells, whereas the number of polyploid CD41(+) cells was reduced significantly. Moreover, activation of VEGFR-3 increased platelet counts in thrombopoietin-treated mice significantly and modulated 5-fluorouracil-induced thrombocytosis strongly, suggesting a regulatory role for VEGFR-3 in megakaryopoiesis.